Production of Palmitoleic and Linoleic Acid in Oleaginous and Nonoleaginous Yeast Biomass - Irena Kolouchová; Olga Maťátková; Karel Sigler; Jan Masák; Tomáš Řezanka (International Journal of Analytical Chemistry)
We investigated the possibility of utilizing both oleaginous yeast species accumulating large amounts of lipids (Yarrowia lipolytica, Rhodotorula glutinis, Trichosporon cutaneum, and Candida sp.) and traditional biotechnological nonoleaginous ones (Kluyveromyces polysporus, Torulaspora delbrueckii, and Saccharomyces cerevisiae) as potential producers of dietetically important major fatty acids. The main objective was to examine the cultivation conditions that would induce a high ratio of dietary fatty acids and biomass. Though genus-dependent, the type of nitrogen source had a higher influence on biomass yield than the C/N ratio. The nitrogen source leading to the highest lipid accumulation was potassium nitrate, followed by ammonium sulfate, which is an ideal nitrogen source supporting, in both oleaginous and nonoleaginous species, sufficient biomass growth with concomitantly increased lipid accumulation. All yeast strains displayed high (70–90%) content of unsaturated fatty acids in total cell lipids. The content of dietary fatty acids of interest, namely, palmitoleic acid and linoleic acid, reached in Kluyveromyces and Trichosporon strains over 50% of total fatty acids and the highest yield, over 280 mg per g of dry cell weight of these fatty acids, was observed in Trichosporon with ammonium sulfate as nitrogen source at C/N ratio 70.